SINTESIS ANALOG 4-BROMO PIRAZOLIN DARI KALKON INTI NAFTALEN DENGAN KATALIS ASAM DAN UJI AKTIVITAS NYA SEBAGAI ANTIBAKTERI - Desy Hariyanti; Hilwan Yuda Teruna; Jasril ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Pyrazolines have been reported to possess  various  biological activities such as antimicrobial,  antidepressant,  antidiabetic,  anti-inflammatory,  antipyretic,  anticancer, and  anticonvulsant  activity. In this research, a halogenated pirazoline 5-(4-bromophenyl)-3-(naphthalene-1-yl)-4,5-dihydro-1H-pyrazole was synthesized  by cyclization  reaction between chalchone with hydrazine  hydrate  using acetate acid as catalyst under microwave irradiation. The compound showed a good yield, and then was characterized by  UV,  IR, 1H-NMR, and 13C-NMR spectroscopy. The antibacterial activity of pyrazolines was determined using the agar diffusion method  against  Gram-negative bacteria:  Escherichia  coli  and  Salmonella  typhi  and  Gram-positive bacteria: Bacillus  subtilis  and  Staphylococcus  aureus. This compound  showed  inhibitory  activity against those four bacteria. Test results of antibacterial activity indicated that pyrazoline analogues were potential as antibiotics.